X-ray microtomography–based atlas of mouse cranial development. Issue 3 (2nd March 2021) - Matula, Jan; Tesarova, Marketa; Zikmund, Tomas; Kaucka, Marketa; Adameyko, Igor; Kaiser, Jozef
Abstract: Background: X-ray microtomography (μCT) has become an invaluable tool for non-destructive analysis of biological samples in the field of developmental biology. Mouse embryos are a typical model for investigation of human developmental diseases. By obtaining 3D high-resolution scans of the mouse embryo heads, we gain valuable morphological information about the structures prominent in the development of future face, brain, and sensory organs. The development of facial skeleton tracked in these μCT data provides a valuable background for further studies of congenital craniofacial diseases and normal development. Findings: In this work, reusable tomographic data from 7 full 3D scans of mouse embryo heads are presented and made publicly available. The ages of these embryos range from E12.5 to E18.5. The samples were stained by phosphotungstic acid prior to scanning, which greatly enhanced the contrast of various tissues in the reconstructed images and enabled precise segmentation. The images were obtained on a laboratory-based μCT system. Furthermore, we provide manually segmented masks of mesenchymal condensations (for E12.5 and E13.5) and cartilage present in the nasal capsule of the scanned embryos. Conclusion: We present a comprehensive dataset of X-ray 3D computed tomography images of the developing mouse head with high-quality manual segmentation masks of cartilaginous nasal capsules. The provided μCT images can be used for studying any other major structure within the developing mouse heads. The high quality of the manually segmented models of nasal capsules may be instrumental to understanding the complex process of the development of the face in a mouse model.